About Counteraction To Extremism And Terrorism In Kazakhstan - Bakhytgul Sembekova, Arstan Akhpanov, Aydarkan Skakov,; Madiyeva, Aygul; Amirgaliyev, Aydos (Opción, 2019)
The comparative and legal analysis of the criminal legislation as a method, gives the grounds to consider terrorism as the extreme form of extremist activity which is mainly realized in the political sphere and shown in violent acts. As a result, acts of terrorism and extremism can be made only with direct intention as the person in this situation realizes public danger of own actions, expects the possibility or inevitability of socially dangerous consequences and wishes their approach. In conclusion, it is important to define the ratio of the concepts terrorism, terrorist activity and terrorist act with the definition extremism.